Quantifying Stratospheric Temperature Signals and Climate Imprints From Post‐2000 Volcanic Eruptions. Issue 21 (3rd November 2019) - Stocker, Matthias; Ladstädter, Florian; Wilhelmsen, Hallgeir; Steiner, Andrea K.
Abstract: Small volcanic eruptions and their effects have recently come into research focus. While large eruptions are known to strongly affect stratospheric temperature, the impacts of smaller eruptions are hard to quantify because their signals are masked by natural variability. Here, we quantify the temperature signals from small volcanic eruptions between 2002 and 2016 using new vertically resolved aerosol data and precise temperature observations from radio occultation. We find characteristic space‐time signals that can be associated with specific eruptions. In the lower stratosphere, robust warming signals are observed, while in the midstratosphere also cooling signals of some eruptions appear. We find that the volcanic contribution to the temperature trend is up to 20%, depending on latitude and altitude. We conclude that detailed knowledge of the vertical structure of volcanic temperature impacts is crucial for comprehensive trend analysis in order to separate natural from anthropogenic temperature changes. Key Points: The imprints of minor volcanic eruptions on stratospheric temperature are precisely quantified Vertically high resolved aerosol and temperature observations facilitate the accurate detection of volcanic signals in space and time Minor volcanic eruptions clearly affect the short‐term temperature trend in the lower stratosphere